Theoretical and experimental analysis of the exact receptance function of a clamped-clamped beam with concentrated masses - Khoa, Nguyen Viet; Thao, Dao Thi Bich (Vietnam Journal of Mechanics, 2020)
This paper establishes the exact receptance function of a clamped-clamped beam carrying concentrated masses. The derivation of exact receptance and the numerical simulations are provided. The proposed receptance function can be used as a convenient tool for predicting the dynamic response at arbitrary point of the beam acted by a harmonic force applied at arbitrary point. The influence of the concentrated masses on the receptance is investigated. The numerical simulations show that peak in the receptance will decrease when there is a mass located close to that peak position. The numerical results have been compared to the experimental results to justify the theory.